2021
DOI: 10.1016/j.nucmedbio.2021.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the plasmid study to relate DNA damaging effects of radionuclides to those from external beam radiotherapy

Abstract: Introduction The biological consequences of absorbed radiation doses are ill-defined for radiopharmaceuticals, unlike for external beam radiotherapy (EBRT). A reliable assay that assesses the biological consequences of any radionuclide is much needed. Here, we evaluated the cell-free plasmid DNA assay to determine the relative biological effects of radionuclides such as Auger electron-emitting [ 67 Ga]GaCl 3 or [ 111 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
3
2
0
Order By: Relevance
“…They justified their results by the fact that the mean free path of free radicals decreases by increase of DNA concentrations. The similar results was reported by Verger et al 55 . They showed that for 5 ng/μL of plasmid, a higher percent of DNA damage was observed than for 1.25 ng/μL plasmid DNA.…”
Section: The Dna Plasmid As a Biodosimeter For Nano‐radiosensitizatio...supporting
confidence: 90%
See 2 more Smart Citations
“…They justified their results by the fact that the mean free path of free radicals decreases by increase of DNA concentrations. The similar results was reported by Verger et al 55 . They showed that for 5 ng/μL of plasmid, a higher percent of DNA damage was observed than for 1.25 ng/μL plasmid DNA.…”
Section: The Dna Plasmid As a Biodosimeter For Nano‐radiosensitizatio...supporting
confidence: 90%
“…The similar results was reported by Verger et al. 55 They showed that for 5 ng/μL of plasmid, a higher percent of DNA damage was observed than for 1.25 ng/μL plasmid DNA. Using different concentration of plasmids, no significant difference in DNA damage was observed by Brabcová et al.…”
Section: The Dna Plasmid As a Biodosimeter For Nano‐radiosensitizatio...supporting
confidence: 90%
See 1 more Smart Citation
“…The influence of the proximity to DNA and accumulation in the cell nucleus on DNA damage and other radiobiological effects was thoroughly investigated for several other AE emitters, namely SPECT radiometals in clinical use such as 67 Ga, 111 In or 99m Tc or less common but more efficient AE emitters such as 195m Pt and 191 Pt [14,15]. For instance, Terry's group demonstrated how the DNA damage induced by 67 Ga and 111 In depends on their proximity to the DNA using a cell-free plasmid DNA assay [16,17]. Several classical DNA intercalators or groove binders have been studied as nuclear-targeting vectors for AE-emitting radionuclides, such as radiolabeled derivatives of acridine orange (AO) [18], pyrene [19], DAPI [20] and doxorubicin [21].…”
Section: Introductionmentioning
confidence: 99%
“…The research papers cover studies in cytogenetics after radium-223 treatment [9], the role of antioxidants in the radiosensitivity to [ 177 Lu]Lu-DOTATATE [10], relating the biological effects of radionuclides such as Auger electron-emitters gallium-67 and indium-111 to that of EBRT [11] and determining the DNA damaging capacity of Auger electron-emitter thallium-201 [12]. The future of Auger electronemitting radiopharmaceuticals was also discussed in a commentary [13].…”
mentioning
confidence: 99%